Socioeconomic Impact of Irrigation Scarcity on the Deprived Community at the Bottom of the Pyramid - Rustum H Darade; Seema Gite-Darade; Manisha Khemnar; Ashvmegha Surve (Archives of Current Research International, 2025)
The impact of irrigation scarcity is not limited to farming alone. It affects different aspects of life, such as education, health, and migration. When farmers cannot grow enough food, their families face food insecurity and malnutrition. Poor nutrition can lead to health problems, making it harder for people to work and earn a living. Children from farming families are often forced to leave school and help with farming or find other jobs to support their households. In extreme cases, families migrate to urban areas in search of work, which results in overcrowded cities and more competition for low-paying jobs. Research Questions: How does irrigation scarcity affect the income and economic stability of BoP communities? How do small farmers and laborers face the key livelihood challenges due to irrigation shortages? How does water scarcity contribute to seasonal or permanent migration among marginalized populations? Aim: 1. To study the impact of irrigation shortage on agricultural yield and income of communities at BoP. 2. To study the impact of irrigation scarcity on employment opportunities in rural areas. 3. To study the migration patterns caused by water scarcity and its impact on families. 4. To study the strategies adopted by the people at the bottom of the pyramid to deal with water scarcity. Methodology Used: A descriptive research design is used to understand and explain the effects of irrigation scarcity on farmers at the bottom of the pyramid. A well-structured questionnaire was distributed to farmers, labourers, and migrant families to collect their responses. The questionnaire includes both close-ended and open-ended questions. A purposive sampling method was used to collect the sample, focusing on communities at the Bottom of the pyramid. Expected Outcome: 1. Clear evidence of how irrigation scarcity affects livelihoods, food security, and migration patterns. 2. Identification of coping strategies used by BoP communities to sustain themselves. 3. Policy recommendations for improving irrigation infrastructure, employment opportunities, and rural resilience.